Auxiliar de ingeniería en la ejecución de la interventoría del proyecto mejoramiento, mantenimiento y rehabilitación corredor vial el túnel las cruces, municipio de Cuitiva adjudicado a la empresa FEYMA INGENIERIA S.A.S (2022)
For civil engineers who are about to graduate from the Antonio Nariño University, it is extremely important to strengthen the knowledge acquired during their training stage, in order to make the process comprehensive and thus achieve the professional goals that are proposed. In the present work the activities that were carried out during the internship in the company FEYMA INGENIERIA S.A.S in the position of engineering assistant in the execution of the intervention project 2575 are presented. With this internship there are two main purposes, the first is to demonstrate to the Boyacá labor market that the UAN students have all the capabilities to compete in the market, achieving the objectives set by each of the companies, and the second is to build the professional path to the next engineers graduated from the UAN.